Judicial review litigation as an incentive to change in local authority public services in England and Wales - Lucinda Platt; Maurice Sunkin; Kerman Calvo (University of Essex, Institute for Social and Economic Research (ISER), 2009)
In this paper we consider the relationship between levels of judicial review litigation and the quality of local government services. The findings indicate that judicial review may be making a positive contribution to local government in England and Wales. The paper also considers the way local government officials perceive judicial review and argues that reactions cannot be wholly understood in terms of incentives. Judicial review makes a positive contribution to public administration at least partly because it promotes values that are central to the ethos of public administration and assists officials in resolving tensions between individual and collective justice.
Keywords: 330